Kinetics and Persistence of the Cellular and Humoral Immune Responses to BNT162b2 mRNA Vaccine in SARS-CoV-2-Naive and -Experienced Subjects: Impact of Booster Dose and Breakthrough Infections - Desmecht, Salomé; Tashkeev, Aleksandr; El Moussaoui, Majdouline; Marechal, Nicole; Perée, Hélène; Tokunaga, Yumie; Fombellida-Lopez, Celine; Polese, Barbara; Legrand, Céline; Wéry, Marie; Mni, Myriam; Fouillien, Nicolas; et al. (Frontiers in Immunology, 2022)
Background: Understanding and measuring the individual level of immune protection and its persistence at both humoral and cellular levels after SARS-CoV-2 vaccination is mandatory for the management of the vaccination booster campaign. Our prospective study was designed to assess the immunogenicity of the BNT162b2 mRNA vaccine in triggering the humoral and the cellular immune response in healthcare workers (HCWs) up to 6 months after two doses vaccination. Methods: This study enrolled 208 HCWs from the Liège University Hospital (CHU) in Belgium. All participants received two doses of BNT162b2 mRNA vaccine. Fifty participants were SARS-CoV-2 experienced and 158 were naïve before vaccination. Blood sampling was performed at the day of the first and second vaccine doses administration, then at 2 weeks, 4 weeks and 6 months after the 1st vaccine dose administration. A total of 1024 blood samples were collected. All samples were tested for the presence of anti-Spike antibodies as well as for neutralizing antibodies against SARS-CoV-2. Cell-mediated immune response was evaluated at T4 on 80 participants by measuring the secretion of IFN- on peripheral blood lymphocytes. All participants were monitored on weekly-basis for the novo SARS-COV-2 infection for 4 weeks after vaccination. Findings: We found that anti-spike antibodies and neutralization capacity levels were significantly higher in SARS-CoV-2 experienced compared to naïve HCWs at all time points analyzed. Cellular immune response was similar in the two groups six months following 2nd dose of the vaccine. Reassuringly, most participants had a detectable cellular immune response to SARS-CoV-2 six months after vaccination. Besides the impact of SARS-CoV-2 infection history on immune response to BNT162b2 mRNA vaccine, we observed a significant negative correlation between age and persistence of humoral response. Cellular immune response was, however, not significantly correlated to age. Conclusions: Our data strengthen previous findings demonstrating that immunization through vaccination combined with natural infection is better than 2 vaccine doses or natural infection alone. It may have implications for personalizing vaccination regimens to prevent severe COVID-19 and reduce the impact of the pandemic on the healthcare system. More specifically, it may help prioritizing vaccination, including for the deployment of booster doses.